Kontribusi Minat dan Kemandirian Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Instalasi Tenaga Listrik - Ellin Desentiya; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study was conducted with the aim of knowing how much the contribution of interest and learning independence to student learning outcomes in the subject of Electrical Power Installation at SMK N 2 Kota Sungai Penuh. This type of research is quantitative using correlation analysis. The subjects in this study were students of class XI TITL at SMK N 2 Kota Sungai Penuh with a total of 29 students consisting of 16 students of class XI TITL 1 and 13 students of class XI TITL 2. The sample determination was carried out by means of Proportional Random Sampling. Data collection using a questionnaire, scoring the questionnaire instrument with a Likert scale then the questionnaire is validated by an expert lecturer validator of the Electrical Engineering Department before being tested and distributed to the main respondents. Data analysis used in the study includes normality test, linearity test and multicollinearity test. Hypothesis testing using a correlation test and hypothesis determination test using a t-test is carried out to test the effect partially between independent and dependent variables. The results showed that there was an influence between the variables of student learning interest on practical learning outcomes in Electrical Power Installation subjects, there was an influence between the variables of student learning independence on practical learning outcomes in Electrical Power Installation subjects, there was an influence between the variables of student learning interest and learning independence together on practical learning outcomes in Electrical Power Installation subjects at SMK 2 Sungai Penuh. So, it can be concluded that Interest and Learning Independence affect Student Learning Outcomes.